The Relationships between Supermassive Black Holes and Star Formation Rate in Active Galaxies using Optical Spectra Variability - Japar, Narjes Abd Al_rhman; Rashed, Y. E. (Iraqi Journal of Science, 2025)
The purpose of this research is to examine the variation in star formation rate for two types of active galaxy models. It also aims to study the relationship between supermassive black holes (SMBH) and the star formation rate (SFR) for 29 samples of active galaxies. These objects have been classified into two types: 19 samples of the Quasar and 10 samples of the Seyferts. These galaxies have been selected from the Sloan Digital Sky Survey (SDSS), at different time intervals, and they have been monitored twice or more times during a period of approximately 10 years. The results in this article show that the value of the standard deviation star formation rate variability with respect to SMBH in QSO is higher than the standard deviation star formation rate variability with respect to SMBH in Seyferts as present, respectively (19.5 and 16.8). Moreover, a good linear correlation has been found between the SMBH and the SFR within the Seyfert and QSO galaxies, exhibiting varying degrees of goodness. This correlation is attributed to the clear impact of the bright active galactic nuclei characteristics among these objects. Additionally, the variability of the emission-lines ([OII], [Hβ], [OIII], [Hα], [SII]) has been studied for both samples (QSO and Seyferts), and it has been found that (([Hβ], [OII], [SII]) are highly affected by the gravitational bound system of the central black hole of the hosting galaxy. Furthermore, it has been noticed that bulge host mass (Mbulge) is linearly correlated with the centrally black hole mass of the host galaxies, leading us to the direct connotation between these parts. On the other hand, no obvious relationship was found between the luminosities at the V-band with respect to the SFR.